Effect of Caffeine Injection on Orthodontic Tooth Movement in Rats: An Experimental Study on Rats - Amin Golshah; Khaled Omidi; Nafiseh Nikkerdar; Fatemeh Ghorbani (Hindawi Limited, 2022)
Objectives. Several studies have investigated the effects of different medications on orthodontic tooth movement (OTM). This study assessed the effect of caffeine injection on OTM in rats. Materials and Methods. Thirty-five male Wistar rats were randomly divided into five groups. Their first molars and central incisors were attached with a nickel-titanium closed coil spring with 50 g load. The rats in the three experimental groups received 25, 50, and 75 mg/kg caffeine intraperitoneally for 21 days. The negative control group did not receive any injection and did not undergo orthodontic treatment. The positive control group underwent orthodontic treatment and received 0.9% NaCl (saline) injection. After 21 days, all rats were sacrificed by chloroform inhalation, and the maxilla was resected. The mean number of Howship's lacunae, blood vessels, osteoclasts, and root resorption lacunae was histologically measured. The bone volume-to-total volume ratio (BV/TV) in maxillary molars was calculated by microcomputed tomography (micro-CT) to quantify bone loss. Results. The amount of OTM and the number of osteoclasts, blood vessels, and Howship's lacunae significantly increased in rats under caffeine therapy, while the number of root resorption lacunae did not increase. Lower BV/TV in the caffeine groups was in accord with the increased count of osteoclasts. Conclusion. Caffeine injection can significantly increase OTM in rats.